Appropriate port selection for floating based offshore wind farms with MCDM Methods: The Case of Turkiye - Canat, Ayse Nuray; Ozkan, Coskun (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2025)
In order for offshore wind power plants, which are one of the renewable energy branches, to provide optimum service, to be low cost and highly beneficial, the installation, operation and maintenance stages should be carried out in a suitable port close to the power plant. In this port selection process, the criteria that ports should have differ according to the turbine structure to be installed. In the literature, there is no study on port location selection for floating wind turbines. In this study, the characteristics that ports should have for the life cycle of floating wind turbines at sea are obtained by examining the studies in the literature. For the selection of suitable ports, the Full Consistency Method (FUCOM), Best Worst Method (BWM), Common Weighting Method, Compromise Ranking of Alternatives from Distance to Ideal Solution Compromise Ranking of Alternatives from Distance to Ideal Solution (CRADIS), Combined Compromise Solution (CoCoSo) and Borda Method were used to contribute to the decision making process. Comparative analyses with other MCDM (Multi-criteria decision making) methods have been carried out to select the appropriate port. In the study, container and Ro-Ro ports in Turkey were used since the port characteristics should be provided at least at minimum level. Samsunport in the Black Sea region was found to be the most suitable port for all three port types (terminal, service and response). The criterion of having a component production facility was found to be the most important criterion for floating based offshore power plant terminal port selection.
Keywords: Port selection for floating offshore wind turbine; Full Consistency Method; Best Worst Method; CRADIS; Combined Compromise Solution; Engineering